Development of a Scalable Process of Film-Coated bi-Layer Tablet Containing Sustained-Release Metoprolol Succinate and Immediate-Release Amlodipine Besylate - Nguyen Thi Linh Tuyen (MDPI AG, 2021)
The development of new drugs that combine active ingredients for the treatment hypertension is critically essential owing to its offering advantages for both patients and manufacturers. In this study, for the first time, detailed development of a scalable process of film-coated bi-layer tablets containing sustained-release metoprolol succinate and immediate-release amlodipine besylate in a batch size of 10,000 tablets is reported. The processing parameters of the manufacturing process during dry mixing-, drying-, dry mixing- completion stages were systematically investigated, and the evaluation of the film-coated bi-layer tablet properties was well established. The optimal preparation conditions for metoprolol succinate layer were 6 min- dry mixing with a high-speed mixer (120 rpm and 1400 rpm), 30-min drying with a fluid bed dryer, and 5-min- mixing completion at 25 rpm. For the preparation of amlodipine besylate layer, the optimal dry-mixing time using a cube mixer (25 rpm) was found to be 5 min. The average weight of metoprolol succinate layers and bi-layer tablets were controlled at 240–260 mg and 384–416 mg, respectively. Shewhart R chart and <semantics><mover accent="true">X¯</mover></semantics> charts of all three sampling lots were satisfactory, confirming that the present scalable process was stable and successful. This study confirms that the manufacturing process is reproducible, robust; and it yields a consistent product that meets specifications.